The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fonc.2023.1179431
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of molecular targeted agents combined with transarterial chemoembolization in the treatment of unresectable hepatocellular carcinoma: a network meta-analysis

Abstract: ObjectiveAt present, several molecular targeted agents(MTAs) combined with transarterial chemoembolization (TACE) have been employed to treat unresectable hepatocellular carcinoma (HCC). In this meta-analysis, we compared the efficacy and safety of different MTAs combined with TACE to enable effective decision-making for the clinical treatment of unresectable HCC.MethodsPubmed, Web of Science, EMBASE, and Cochrane Library were retrieved to evaluate the efficacy and safety of different MTAs combined with TACE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Furthermore, there were no significant differences in the survival advantage between sorafenib with TACE and lenvatinib monotherapy in the present NMA. Similar results have been reported by other studies ( 16 , 30 , 33 ). However, considering the increased survival outcomes of lenvatinib monotherapy compared with sorafenib monotherapy and the lack of a direct comparison between lenvatinib and sorafenib with TACE in the currently available studies, more head-to-head research is needed to further explore the superiority of survival outcomes ( 12 , 34 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, there were no significant differences in the survival advantage between sorafenib with TACE and lenvatinib monotherapy in the present NMA. Similar results have been reported by other studies ( 16 , 30 , 33 ). However, considering the increased survival outcomes of lenvatinib monotherapy compared with sorafenib monotherapy and the lack of a direct comparison between lenvatinib and sorafenib with TACE in the currently available studies, more head-to-head research is needed to further explore the superiority of survival outcomes ( 12 , 34 ).…”
Section: Discussionsupporting
confidence: 93%
“…A recent NMA included 10 RCTs and 35 cohort studies and compared the efficacy and safety of TKIs in combination with TACE in the treatment of uHCC ( 16 ). The lenvatinib with TACE combination therapy had a significantly longer PFS (HR, 0.53; 95% CI, 0.32–0.88) but not OS (HR, 0.88; 95% CI, 0.65–1.13), when compared with sorafenib with TACE group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LEN specifically targets vascular endothelial growth factor receptors (VEGF) 1–3 and fibroblast growth factor receptors (FGFR) 1–4, offering the potential for a higher response rate compared to other MTAs [ 6 ]. However, as the therapeutic effect of LEN monotherapy in patients with u-HCC is limited, there is growing interest in exploring the strategy of combining LEN with other therapies [ 7 , 8 ]. We previously reported that the combination of LEN with transcatheter intra-arterial therapies (TIT), such as transcatheter arterial chemoembolization (TACE) and hepatic arterial infusion chemotherapy (HAIC), improved the prognosis of patients with intermediate-stage HCC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%